Causes and Consequences of Metabolic Acidosis in Patients after Kidney Transplantation - Alexander Ritter; Nilufar Mohebbi (Karger Publishers, 2020)
Background: Metabolic acidosis (MA) is a common complication in kidney transplantation (KTx). It is more prevalent in KTx than in CKD, and it occurs at higher glomerular filtration rates. The pathophysiologic understanding of MA in KTx and its clinical impact has been highlighted by few recent studies. However, no guidelines exist yet for the treatment of MA after KTx. Summary: MA in KTx seems to share pathophysiologic mechanisms with CKD, such as impaired ammoniagenesis. Additional kidney transplant-specific factors seem to alter not only the prevalence but also the phenotype of MA, which typically shows features of renal tubular acidosis. There is evidence that calcineurin inhibitors, immunological factors, process of donation, donor characteristics, and diet may contribute to MA occurrence. According to several mainly observational studies, MA seems to play a role in disturbed bone metabolism, cardiovascular morbidity, declining graft function, and mortality. A better understanding of the pathophysiology and evidence from randomized controlled trials, in particular, are needed to clarify the role of MA and the potential benefit of alkali treatment in KTx. Alkali therapy might not only be beneficial but also cost effective and safe. Key Messages: MA seems to be associated with several negative outcomes in KTx. A deeper understanding of the pathophysiology and clinical consequences of MA in KTx is crucial. Clinical trials will have to determine the potential benefits of alkali therapy.